Effect of liming, manure, and NPK fertilizer application on growth and yield performance of soybean in swamp land - A Wijanarko; A Taufik; D Harnowo (Brawijaya University, 2016)
Increased productivity and the expansion of planting area to potential land are two strategies to increase soybean production. Swamp land is one of potential land. Acidic soil, poor fertility, and toxicity become limiting factors for soybean development in this area. Objective of this research was to determine effect of liming, organic and NPK fertilizer application on soybean yields in swamp land. On-farm trial had been conducted on swamp land of C type in South Kalimantan. Treatments consisted of two factors, laid out in randomized complete block design, replicated three times. The fist factor was three doses of manure (0, 2.5, and 5.0 t/ha). The second factor was four combinations of NPK fertilization dosage, (1) 0-0-0, (2) 22,5-36-30, (3) 22,5-54-60, and (4) 45-72-60 kg N-P2O5-K2O per hectare. Combinations of these two factors were tested on two environments, without and with liming. Results revealed that soil acidity, poor P, K, Ca, and Mg, and high aluminum saturation became limiting factors for soybean growth and yield in swamp land of type C in South Kalimantan. Amelioration using 2.5 t/ha manure, liming with dolomite equivalent to 20% of Al saturation, and NPK fertilizer at dose of 45 kg N - 72 kg K2O – 60 kg P2O5 /ha improved soil properties and soybean growth, and increase productivity to 2.4 t/ha.